2018
DOI: 10.3390/v10120710
|View full text |Cite
|
Sign up to set email alerts
|

The N-Terminus of the HIV-1 p6 Gag Protein Regulates Susceptibility to Degradation by IDE

Abstract: As part of the Pr55Gag polyprotein, p6 fulfills an essential role in the late steps of the replication cycle. However, almost nothing is known about the functions of the mature HIV-1 p6 protein. Recently, we showed that p6 is a bona fide substrate of the insulin-degrading enzyme (IDE), a ubiquitously expressed zinc metalloprotease. This phenomenon appears to be specific for HIV-1, since p6 homologs of HIV-2, SIV and EIAV were IDE-insensitive. Furthermore, abrogation of the IDE-mediated degradation of p6 reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 83 publications
(139 reference statements)
0
4
0
Order By: Relevance
“…However, in this study, no significant differences were observed in the frequency of PT/SAP duplication between KSB (4.3% or 4/94) and subtype B-infected patients (12.5% or 2/16). Recently, the importance of p6 Gag protein as a substrate of the insulin-degrading enzyme has been investigated [21].…”
Section: Discussionmentioning
confidence: 99%
“…However, in this study, no significant differences were observed in the frequency of PT/SAP duplication between KSB (4.3% or 4/94) and subtype B-infected patients (12.5% or 2/16). Recently, the importance of p6 Gag protein as a substrate of the insulin-degrading enzyme has been investigated [21].…”
Section: Discussionmentioning
confidence: 99%
“…The competitive substrate insulin or the 6bK-mediated inhibition of IDE resulted in reduced virus replication. Likewise, HIV-1 harboring IDE-insensitive p6 mutants or a naturally occurring polymorphism of HIV-1 p6 showed reduced virus replication capacity [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the gE/IDE interaction was not necessary for VZV infection of T cells in vivo [ 113 ]. On the other hand, IDE is necessary and sufficient for degradation of the mature p6 protein of the human immunodeficiency virus 1 (HIV-1) [ 102 , 114 ]. Of note, p6 is degraded 100-fold more efficiently than insulin [ 102 ].…”
Section: Introductionmentioning
confidence: 99%